Two new deep-sea squat lobsters of the genus Munidopsis Whiteaves, 1874 (Crustacea: Decapoda: Munidopsidae) from Taiwan - Lin, Chia-Wei; Chan, Tin-Yam (Zootaxa, 2011)
Two new deep-sea munidopsids, Munidopsis aurantia sp. nov. and M. laevisquama sp. nov., are described from Taiwan. Munidopsis aurantia sp. nov. closely resembles M. serricornis (Lovén, 1852), but differs in lacking an antennal spine, cheliped with fingers longer than palm and merus bearing distal spines but without a row of dorsal spines. Munidopsis laevisquama sp. nov. differs from other congeners by its carapace being densely covered with squamae but without dorsal spines, eyes that are subglobular and lacking spines or papillae, the basal antennal segment bearing a cylindrical process, and the cheliped and walking legs all lacking distal spines. Altogether 36 species of Munidopsis are now known from the deep waters off Taiwan.